The Pursuit of Universality in Chinese Buddhism - Zhu Cheng (Religions)
Having adopted, appropriated, and altered Indian forms of Buddhism, various schools of Chinese Buddhist thought inherited and transformed essential orientations of both Buddhism and traditional Chinese philosophy insofar as it exhibits a tendency toward seeking universality in its understanding of the world. Within the works of prominent figures and schools such as Sengzhao and the Tiantai school, Huayan, the Consciousness-Only school, and Chan Buddhism, Chinese Buddhist thought integrates the diversity of phenomena through the notion of a unifying “mind-consciousness”. This approach creates the framework for understanding the relationship between humans and all things based on the comprehensive nature of consciousness. Given this foundation, Chinese Buddhist thought places a high value on the equality of all beings, advocates for dismantling distinctions between individuals and the world, and transcends the distinctions of reality to pursue universal unity. By dissolving the boundaries of existence and non-existence, the self and things, and the individual ego, this philosophical outlook lays a cognitive foundation for eradicating the “discriminating mind” in daily life and offers insights into overcoming separatism and isolationism. The Chinese Buddhist pursuit of universal consistency, which is simultaneously of this world yet transcendent, reflects Buddhism’s profound concern for humanity’s shared destiny.